Separation of oil/water emulsions in continuous flow using microwave heating - Binner, Eleanor; Robinson, John P.; Kingman, S.W.; Lester, Edward; Azzopardi, Barry J.; Dimitrakis, Georgios; Briggs, John (American Chemical Society, 2013)
This work studies a continuous flow microwave system to enhance gravity settling of water-in-oil emulsions. Settling times were found to be dependent upon the applied power, flowrate and energy input. Power and energy input are linked to liquid flowrate within the flow system used in this study, so a key objective of this work was to understand the effect of turbulence on the heating and separation of the flowing emulsion. At high flowrates (9 – 12 L/min) it was found that turbulence dominates, with settling times largely independent of energy input. At lower flowrates (1 - 6 L/min), when turbulence was decreased, it was found that the settling time decreased as the power density was increased. Settling times have the potential to be less than half that of untreated emulsions, and can be reduced further if turbulence can be minimised between the microwave heating zone and the settling zone in the process equipment.